Hantu Perempuan Jawa dalam Alaming Lelembut Sebagai Representasi Femme Fatale - Halimah, Umi (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
This study entitled â€œThe Javanese Female Ghost in â€žAlaming Lelembutâ€Ÿ as a Representation of Femme Fataleâ€aims to show the feminist value in Javanese horror stories with female ghost as a villain and men as most of their victims. This study uses feminism as a main approach and femme fatale theory as the specific approach theory. This study shows that there are three kinds of of female ghost, they are female ghosts who experienced a miserable life before her death, sensual women and women whose background is not known. For the three kinds of women it can be revealed the causes of the female spirits to become evil spirits, the modes of female ghosts to ensnare and trap victims, the female ghostâ€Ÿs harmful effects to men, and the solutions as the anti-climac in the story.